Methods for comparing durability of immune responses between vaccine regimens in early-phase trials. (January 2020) - Westling, Ted; Juraska, Michal; Seaton, Kelly E.; Tomaras, Georgia D.; Gilbert, Peter B.; Janes, Holly
The ability to produce a long-lasting, or durable, immune response is a crucial characteristic of many highly effective vaccines. A goal of early-phase vaccine trials is often to compare the immune response durability of multiple tested vaccine regimens. One parameter for measuring immune response durability is the area under the mean post-peak log immune response profile. In this paper, we compare immune response durability across vaccine regimens within and between two phase I trials of DNA-primed HIV vaccine regimens, HVTN 094 and HVTN 096. We compare four estimators of this durability parameter and the resulting statistical inferences for comparing vaccine regimens. Two of these estimators use the trapezoid rule as an empirical approximation of the area under the marginal log response curve, and the other two estimators are based on linear and nonlinear models for the marginal mean log response. We conduct a simulation study to compare the four estimators, provide guidance on estimator selection, and use the nonlinear marginal mean model to analyze immunogenicity data from the two HIV vaccine trials.